Pelaksanaan Restorative Justice Dalam Tindak Pidana Penganiayaan di Kejaksaan Negeri Surakarta - Anggita Vristia Hapsari; Evi Ariyani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
Many cases with a small percentange of losses tend to be processed till imprisonment. Limited prison capacity with an excessive number of inmates will become a consequence namely over capacity of inmates in correctiona institutions in. With the occurrence of over capacity in correctional institutions, the costs incurred by the state for convits will also be even greater. This research was conducted to examine whether the implementation of Restorative Justice at the Surakarta Prosecutor’s Office was in accordance with the Attorney General’s Regulation Number 15 of 2020. The research method used qualitative and the type research was field research. The research location was at the Surakarta State Prosecutor’s Ofice. The data analysis tecniques in this research used analysis according to Miles and Huberman. The result of this research explain that the termination of prosecution carried out by the Surakarta Prosecutor’s Office is in accordance with the Attorney General’s Regulation Number15 of 2020. The application of Restorative Justice in Islamic criminal law can also be seen in the imposition of sanctions for jarimah qisas and diyat. Forgiveness given by the victims or his families can abort the qisas sentence. Through the concept of diyat, compensation for the consequences of crime can be felt directly by victims or their families.